Method for preparing fine-grain high-plasticity Ta-W alloy plate

By adding Sc2O3 powder to Ta-W alloy and using high-temperature multi-directional reciprocating die forging and free forging, combined with steel plate coating and hot rolling, the problems of difficult preparation of sintered strips, coarse grains and poor plasticity during the smelting process are solved, and the plasticity and grain refinement of the material are significantly improved.

CN119553161APending Publication Date: 2025-03-04NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411768766.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

During the smelting process, existing Ta-W alloys have problems such as difficult preparation of sintered strips, coarse grains and poor plasticity, especially when they are prone to oxidation at high temperatures, resulting in burn loss and performance differences in the material during thermal processing.

Method used

By adding Sc2O3 powder to the raw material, fine crystal Ta-W alloy ingot structure is prepared, and high-temperature multi-directional reciprocating die forging and free forging are used to eliminate columnar crystals after casting. At the same time, steel plates are coated with hot rolling to prevent oxidation, ensure uniform tissue and fine grains.

Benefits of technology

The plasticity of Ta-W alloy sheet was significantly improved, and the grain size was reduced from the original 2mm to 3mm to 15μm to 30μm, and the elongation was increased to 28% to 46%, which solved the problem of coarse grains and poor plasticity after smelting and processing of tantalum tungsten alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553161A_ABST
    Figure CN119553161A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a fine-grain high-plasticity Ta-W alloy plate, which comprises the following steps of: adding Sc2O3 powder into Ta-W alloy preparation raw materials, uniformly mixing, then carrying out electron beam melting, and carrying out multidirectional reciprocating die forging, free forging and package rolling to prepare the Ta-W alloy plate. The Sc2O3 powder is added into the raw materials to obtain a fine-grain Ta-W alloy ingot structure, high-temperature multi-direction reciprocating die forging is combined to eliminate columnar crystals after casting to enable the structure to be more uniform, then steel plate coating hot rolling is adopted, oxidation of the Ta-W alloy plate is effectively prevented, and therefore the Ta-W alloy plate is uniform in structure, fine in grain and high in yield. The plasticity of the Ta-W alloy plate is greatly improved, and the TaW10 alloy, the TaW12 alloy and the TaW13 alloy prepared through the method serve as high-temperature structures and functional materials and are suitable for the fields of weapons, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of high-temperature structures and functional materials of refractory metal alloys, and in particular relates to a method for preparing a fine-grained high-plasticity Ta-W alloy plate. Background Art

[0002] Ta-W alloy is a continuous solid solution single-phase binary alloy composed of high-density, high-melting-point tantalum and tungsten. It is a very important type of tantalum alloy and is used in some extremely harsh working conditions such as high temperature resistance, impact resistance and corrosion resistance. High-tungsten tantalum alloy generally refers to Ta-W alloy with a W content of more than 8%. It has higher room temperature and high temperature strength. Therefore, these tantalum-tungsten alloys are better candidate materials for heat-resistant erosion components. Because of their high density, high melting point, good corrosion resistance, good processability and weldability, they have been gradually used in weapons, aerospace and other fields in recent years. At present, the mature high-tungsten tantalum alloys are mainly TaW10 and TaW12, while TaW13 alloy is still in the laboratory research stage. As a refractory metal alloy, it is generally prepared by vacuum electron beam melting. The tungsten-tantalum ingot melted by electron beam has low impurities and interstitial elements, uniform composition, and the oxygen content can be easily controlled below 0.01%. However, there are two major difficulties in electron beam melting of Ta-W alloys: (1) It is difficult to prepare the sintered bars used for melting. Since Ta and W are both high melting point and high specific gravity elements, they are both difficult to sinter. Generally, the solid phase sintering density is low, which makes melting impossible, while liquid phase sintering requires a higher temperature, which the equipment cannot reach; (2) The electron beam ingot has coarse grains. The grain size of the electron beam melting ingot of tantalum-tungsten alloy can reach 2mm to 3mm or more. The coarse grains seriously affect the strength and plasticity of the tantalum-tungsten alloy, which must be properly improved by extrusion or forging. Generally, the grain size of the Ta-W alloy melted by electron beam is 90μm to 130μm after extrusion, forging, rolling and other pressure processing, and the elongation is 15% to 30%. This index is still a certain distance from the actual engineering needs. Due to its high strength and easy oxidation, high tungsten tantalum alloy makes pressure processing and forming difficult. Hot processing such as extrusion, forging and hot rolling is often carried out at temperatures above 1000℃, or even higher. Tantalum-tungsten alloys are easy to oxidize at high temperatures. The burning of materials during hot working due to high-temperature oxidation seriously reduces the material yield, deteriorates the surface condition of forgings, and has an adverse effect on subsequent processing. During the hot rolling process, the surface layer is oxygenated and hardened, which increases the difference in the organizational properties and mechanical properties inside and outside the workpiece: the inside is low-oxygen and high-plastic, and the outer layer is in a high-oxygen hardened state. In addition, the difference in temperature inside and outside causes the plasticity of the outer layer of the workpiece to deteriorate. The large deformation flow inside the material will eventually tear the difficult-to-deform surface, seriously affecting the yield rate of the plate. At the same time, due to the presence of the oxygen-absorbing layer, the plasticity of the material deteriorates, and the elongation can only reach about 15% to 30%. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing fine-grained high-plasticity Ta-W alloy sheet in view of the deficiencies of the above-mentioned prior art. The method obtains a fine-grained Ta-W alloy ingot structure by adding Sc2O3 powder to the raw material, and combines high-temperature multi-directional reciprocating die forging and free forging to eliminate columnar crystals after casting to make the structure more uniform, and then uses steel plate coating and hot rolling to prevent the oxidation of the Ta-W alloy sheet, so that the Ta-W alloy sheet has a uniform structure and refined grains, greatly improving the plasticity of the Ta-W alloy sheet, and solving the problem of coarse grains and poor plasticity after tungsten-tantalum alloy smelting and processing.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing fine-grained and high-plasticity Ta-W alloy plate, characterized in that, in this method, Sc2O3 powder is added to the Ta-W alloy preparation raw material and mixed to prepare a sintered bar, and then electron beam melting is performed, and then multi-directional reciprocating die forging plus free forging and jacket rolling are performed to prepare the Ta-W alloy plate; the material of the Ta-W alloy plate is TaW10, TaW12 or TaW13 alloy with a high W content.

[0005] The above-mentioned method for preparing a fine-grained high-plasticity Ta-W alloy sheet is characterized in that the method comprises the following steps:

[0006] Step 1: Place Ta powder, W powder and Sc2O3 powder in a mixer and mix them evenly, and press them into billets, and place the billets in a vacuum carbon tube furnace for high-temperature sintering to obtain sintered billets;

[0007] Step 2: subjecting the sintered bar obtained in step 1 to electron beam melting twice to obtain a Ta-W alloy ingot;

[0008] Step 3: split the Ta-W alloy ingot obtained in step 2, and then perform high-temperature multi-directional reciprocating die forging and free forging using a forging hammer or a press to obtain a forging blank;

[0009] Step 4, machining the forging blank obtained in step 3 to remove defects;

[0010] Step 5: The forging blank after the defects are removed in step 4 is covered with a steel plate for welding, and then hot rolled to obtain a Ta-W alloy plate.

[0011] First, the present invention adds Sc2O3 powder when preparing sintered bars, and utilizes the O element in Sc2O3 to combine with the impurities C, S and other elements in Ta powder and W powder to remove impurities. Due to the difference in the atomic radius of Sc and the atomic radius of Ta, the matrix lattice will be distorted after infiltration, thereby generating a certain number of defects such as dislocations and vacancies, which provides a fast diffusion channel for W atoms, promotes the densification of the sintered bars and the homogenization of the W element. At the same time, since Ta and W are both difficult to sinter materials, and Sc has a relatively low melting point, it has liquid phase flow during the sintering process, which promotes the densification of the sintered bars. In addition, when the sintered bars containing a small amount of Sc2O3 are subsequently electron beam melted, more high-melting point fine compounds and solutes rich in Sc atoms are pushed to the solid-liquid interface during the solidification process and enriched there, causing the solute concentration here to increase, resulting in an increase in the supercooling of the components, hindering the growth of the solidified crystal phase in the molten pool. As the melting continues, the Sc element evaporates completely, while the grains remain fine during solidification, thereby obtaining a fine-grained Ta-W alloy ingot.

[0012] Secondly, although the grains of the Ta-W alloy ingot are refined after adding Sc2O3, a large number of cast columnar crystals are still retained, which usually requires extrusion to open the blank. The extrusion temperature of rare refractory metal materials is high and the extrusion speed is fast, so the extrusion equipment and molds are very demanding. In this regard, the present invention adopts a process of directly forging and opening the blank after smelting, so that the cast columnar crystals are broken to improve plasticity. Since the conventional forging flattening and shaping free forging method is difficult to form three-dimensional compressive stress to fully break the grains, the present invention adopts high-temperature multi-directional reciprocating die forging plus free forging upsetting, and the three-dimensional compressive stress generated by simulating extrusion fully breaks the columnar crystals produced by casting, forming a fine and uniform microstructure, thereby obtaining a fine-grained forging blank.

[0013] Again, tantalum and tantalum alloys begin to absorb oxygen above 400°C. Oxygen has a solid solution strengthening effect in tantalum and tantalum alloys, increasing their hardness by 1 to 3 times, but greatly reducing the plasticity of tantalum and tantalum alloys. Therefore, the oxygen dissolved in tantalum and tantalum alloys, as a harmful element that damages plastic toughness, should be reduced or removed as much as possible, and the defects and oxygen absorption layer must be removed cleanly after high-temperature forging before the next step of processing. In this regard, the present invention adopts a coating rolling process, encapsulating the forging blank in a steel plate sheath, and hot rolling is performed after heat preservation in a heating furnace, so that the sheath and the forging blank are deformed at the same time. After rolling is completed, the sheath can be removed with dilute hydrochloric acid. During the rolling process, due to the protection of the sheath, the forging blank has no oxidation and cracks, which effectively avoids the oxidation of the Ta-W alloy plate during hot rolling, purifies the grain boundary, and combines with subsequent vacuum heat treatment to achieve recrystallization annealing, greatly improving the plasticity of the Ta-W alloy plate.

[0014] The above method for preparing fine-grained high-plasticity Ta-W alloy sheet is characterized in that the particle size of the Ta powder and W powder in step 1 does not exceed 320 mesh, the particle size of the Sc2O3 powder does not exceed 500 mesh, and the mass of the Sc2O3 powder added is 0.05% to 0.1% of the total mass of the Ta powder, W powder and Sc2O3 powder. The present invention controls the addition of a trace amount of Sc2O3 powder so that it evaporates completely after smelting, and maintains the original composition of the Ta-W alloy.

[0015] The above method for preparing fine-grained high-plasticity Ta-W alloy sheet is characterized in that the high-temperature sintering system in step 1 is: in a vacuum degree not exceeding 5.0×10 -1 Pa, firstly, the temperature is raised to 1700°C within 3 hours and kept at this temperature for 4 hours, then the temperature is raised to 2100°C to 2400°C within 1 hour and kept at this temperature for 6 hours to 8 hours, the pre-alloying is completed, and then the furnace temperature is lowered to below 100°C before being taken out of the furnace. The present invention controls the high-temperature sintering system, and gradually removes oxygen, nitrogen, hydrogen gas impurities and low-melting-point, volatile elements by means of staged heating, so that each raw material powder forms a stable and dense structure after pre-alloying, and the furnace temperature is lowered to below 100°C before being taken out of the furnace to effectively prevent oxidation.

[0016] The above method for preparing a fine-grained high-plasticity Ta-W alloy plate is characterized in that the sintered bars in step 2 are bundled into electrodes and then subjected to vacuum electron beam melting twice, wherein the speed of the first vacuum electron beam melting is 30kg / h to 60kg / h, the speed of the second vacuum electron beam melting is 25kg / h to 45kg / h, the speeds of the two vacuum electron beam melting are successively reduced, the melting power is 70kW to 190kW, and the melting vacuum degree does not exceed 1.0×10 -1 Pa. Preferably, the speed of the first vacuum electron beam melting is 38 kg / h to 55 kg / h, the speed of the second vacuum electron beam melting is 33 kg / h to 40 kg / h, and the melting power is 80 kW to 180 kW.

[0017] The above-mentioned method for preparing fine-grained high-plasticity Ta-W alloy sheet is characterized in that the high-temperature multi-directional reciprocating die forging plus free forging in step 3 is heated to 1100°C to 1300°C by a resistance furnace, the holding time is 50 minutes, the final forging temperature is 900°C, and the multi-directional die forging is performed by a tumbling die for no less than 2 times, the inner diameter D of the tumbling die used in each adjacent forging pass is 5mm to 10mm apart, the chamfer R at the tumbling die opening is (0.4 to 0.5)D, and the forging blank upsetting ratio is less than 1.7. The present invention uses high-temperature multi-directional reciprocating die forging plus free forging to fully crush the coarse grains in the Ta-W alloy ingot and reach the limit of deformation within one fire; usually, the round ingot deformed by multi-directional forging is finally shaped into a square forging blank with a thickness of 35mm to 55mm.

[0018] The above-mentioned method for preparing fine-grained high-plasticity Ta-W alloy plate is characterized in that in step 4, a planer is used to plane 3mm to 5mm thick on the six surfaces of the forging blank until the oxide scale and crack defects are completely removed.

[0019] The above-mentioned method for preparing fine-grained high-plasticity Ta-W alloy plate is characterized in that the steel plate sheath material in step five is Q235 steel, with a thickness of 2mm to 3mm, and argon arc welding is adopted; the heating temperature of the hot rolling is 800℃ to 1100℃, the holding time is 50min, the deformation per pass is 5% to 15%, and the rolling equipment used is a two-roll or four-roll plate rolling mill.

[0020] The above method for preparing fine-grained high-plasticity Ta-W alloy sheet is characterized in that after hot rolling in step 5, the steel sheet sheath is removed by using dilute hydrochloric acid, and then vacuum heat treatment is performed. The vacuum heat treatment system is: heat preservation at 1280°C to 1500°C for 1h to 3h, and the vacuum degree is maintained at 5.0×10 -2 Pa~5×10 - 4 Pa.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] 1. The present invention prepares sintered bars by adding Sc2O3 powder to the raw materials, which promotes the densification of the sintered bars and the homogenization of the W element, and hinders the grain growth during smelting, thereby obtaining a fine-grained Ta-W alloy ingot structure. After smelting, the Sc element is completely volatilized without residue, and has no effect on the original alloy composition.

[0023] 2. The present invention adopts high-temperature multi-directional reciprocating die forging plus free forging upsetting to simulate the three-dimensional compressive stress generated by extrusion, thereby increasing the deformation of the Ta-W alloy ingot during the forging process, fully crushing the columnar crystals generated by casting, forming a fine and uniform microstructure, thereby obtaining a fine-grained forging billet, while eliminating the extrusion process, the process is simple and easy to implement.

[0024] 3. The present invention adopts a steel plate cladding rolling method, which effectively avoids oxidation of the Ta-W alloy plate during hot rolling, purifies the grain boundaries, and greatly improves the plasticity of the Ta-W alloy plate.

[0025] 4. The equipment used in the present invention are all commonly used equipment in the industry. No special equipment is required, the equipment requirements are not high, and the condition control process is simple and easy to implement.

[0026] 5. The grain size of the Ta-W alloy plate prepared by the present invention is 15μm to 30μm, and the elongation after fracture is 28% to 46%, which is more than 80% higher than that of the conventional method. It is suitable for high-temperature structural parts in the fields of weapons, aviation, and aerospace.

[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a physical picture of the forging blank prepared in Example 3 of the present invention being wrapped with steel plates, welded and rolled.

[0029] Figure 2 This is the SEM image of the tensile fracture of the TaW12 alloy plate prepared in Example 3 of the present invention.

[0030] Figure 3 This is the metallographic diagram of the TaW12 alloy plate prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0031] Example 1

[0032] This embodiment includes the following steps:

[0033] Step 1: Place Ta powder, W powder and Sc2O3 powder in a mixer and mix them evenly, and press them into billets with a size (width×height×length) of 17mm×17mm×400mm. Place the billets in a vacuum carbon tube furnace for high-temperature sintering to obtain grayish white, slightly yellowish and curved sintered bars;

[0034] The particle size of the Ta powder and the W powder does not exceed 320 meshes, the particle size of the Sc2O3 powder does not exceed 500 meshes, and the mass of the Sc2O3 powder added is 0.1% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, the mass of the W powder added is 8% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, and the balance is Ta powder;

[0035] The high temperature sintering system is: in a vacuum degree not exceeding 5.0×10 -1 Pa, firstly, the temperature is raised to 1700℃ within 3h and kept at this temperature for 4h, then raised to 2100℃ within 1h and kept at this temperature for 6h to complete the pre-alloying, and then the furnace temperature is lowered to below 80℃ before being taken out of the furnace;

[0036] Step 2: After bundling the sintered bars obtained in step 1 into electrodes, perform vacuum electron beam melting twice, wherein the speed of the first vacuum electron beam melting is 60 kg / h, the melting power is 80 kW, the speed of the second vacuum electron beam melting is 45 kg / h, the melting power is 140 kW, the speeds of the two vacuum electron beam meltings are successively reduced, and the melting vacuum degree does not exceed 1.0×10 -1Pa, and obtain a TaW10 alloy ingot with a diameter of 90 mm;

[0037] Step 3, the TaW10 alloy ingot obtained in step 2 is divided, polished to remove surface defects and coated with a high-temperature anti-oxidation coating, placed in a silicon carbon rod resistance furnace, heated to 1100°C and kept warm for 50 minutes, and then high-temperature multi-directional reciprocating die forging and free forging are performed using an air hammer, two die-throwing and drawing are used, the inner diameter D of the die bore used in adjacent forging passes is 10 mm apart, the chamfer R at the die opening is 0.5D, and after two upsetting and drawing, it is flattened and squared, the upsetting ratio of the forging blank is 1.6, and the final forging temperature is 900°C to obtain a forging blank;

[0038] Step 4: Use a planer to plane off 3mm thickness from the six faces of the forging blank obtained in step 3, and then thoroughly grind away the crack defects;

[0039] Step 5: The forged blank after grinding in step 4 is completely covered with a steel plate sheath. The steel plate sheath is made of Q235 steel with a thickness of 2 mm. Argon arc welding is adopted, and then the blank is placed in a resistance muffle furnace and heated to 800°C. The holding time is 50 min. The blank is hot rolled with a two-roll plate rolling mill with a pass deformation of 15% and a total deformation of 75%. The steel plate sheath is then removed with dilute hydrochloric acid, and vacuum annealing is performed. The vacuum annealing system is: keeping at 1280°C for 1.5 h, and the vacuum degree is maintained at not less than 5.0×10 -3 Pa, and a TaW10 alloy plate with a thickness of 10 mm was obtained.

[0040] Samples were taken from the TaW10 alloy plate prepared in this embodiment, and room temperature mechanical property tests and microstructure analyses were performed, respectively. The performance of the samples was then compared with that of the TaW10 alloy plate prepared by the conventional process widely used in the industry, i.e., sintering and smelting of Ta powder and W powder followed by extrusion, conventional forging, and rolling. The results are shown in Table 1 below.

[0041] Table 1

[0042]

[0043] It can be seen from Table 1 that the average grain size of the TaW10 alloy plate prepared in this embodiment is significantly lower than that of the TaW10 alloy plate prepared by the conventional process, and the tensile strength is improved, and the elongation and cross-sectional shrinkage are greatly improved.

[0044] Example 2

[0045] This embodiment includes the following steps:

[0046] Step 1: Place Ta powder, W powder and Sc2O3 powder in a mixer and mix them evenly, and press them into billets with a size (width×height×length) of 17mm×17mm×400mm. Place the billets in a vacuum carbon tube furnace for high-temperature sintering to obtain grayish white, slightly yellowish and curved sintered bars;

[0047] The particle size of the Ta powder and the W powder does not exceed 320 meshes, the particle size of the Sc2O3 powder does not exceed 500 meshes, and the mass of the Sc2O3 powder added is 0.05% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, the mass of the W powder added is 10.8% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, and the balance is Ta powder;

[0048] The high temperature sintering system is: in a vacuum degree not exceeding 5.0×10 -1 Pa, firstly, the temperature is raised to 1700℃ within 3h and kept at this temperature for 5h, then raised to 2400℃ within 1h and kept at this temperature for 8h to complete the pre-alloying, and then the furnace temperature is lowered to below 80℃ before being taken out of the furnace;

[0049] Step 2: After bundling the sintered bars obtained in step 1 into electrodes, perform vacuum electron beam melting twice, wherein the speed of the first vacuum electron beam melting is 38 kg / h, the melting power is 120 kW, the speed of the second vacuum electron beam melting is 33 kg / h, the melting power is 180 kW, the speeds of the two vacuum electron beam meltings are successively reduced, and the melting vacuum degree does not exceed 1.0×10 -1 Pa, and obtain a TaW13 alloy ingot with a diameter of 90 mm;

[0050] Step 3, the TaW13 alloy ingot obtained in step 2 is divided, polished to remove surface defects and coated with a high-temperature anti-oxidation coating, placed in a silicon carbon rod resistance furnace, heated to 1300°C and kept warm for 50 minutes, and then a press is used for high-temperature multi-directional reciprocating die forging and free forging, two times of die throwing and drawing are used, the inner diameter D of the die bore used in adjacent forging passes is 5mm apart, the chamfer R at the die opening is 0.5D, and after two times of upsetting and drawing, it is flattened and squared, the upsetting ratio of the forging blank is 1.4, and the final forging temperature is 900°C to obtain a forging blank;

[0051] Step 4: Use a planer to plane off 5 mm thickness from the six faces of the forging blank obtained in step 3, and then thoroughly grind away the crack defects;

[0052] Step 5: The forged blank after grinding in step 4 is completely covered with a steel plate sheath. The steel plate sheath is made of Q235 steel with a thickness of 3 mm. It is welded by argon arc welding, and then placed in a resistance muffle furnace and heated to 1100°C. The holding time is 50 min. The two-roll plate rolling mill is used for hot rolling with the sheath. The pass deformation is 5% and the total deformation is 73%. Then, the steel plate sheath is removed with dilute hydrochloric acid, and vacuum annealing is performed. The vacuum annealing system is: keep warm at 1500°C for 3 hours, and keep the vacuum degree not less than 5.0×10 -3 Pa, and a TaW13 alloy plate with a thickness of 11 mm was obtained.

[0053] Samples were taken from the TaW13 alloy plate prepared in this embodiment, and room temperature mechanical property tests and microstructure analyses were performed, respectively. The performance of the samples was then compared with that of the TaW13 alloy plate prepared by the conventional process widely used in the industry, i.e., sintering and smelting of Ta powder and W powder followed by extrusion, conventional forging, and rolling. The results are shown in Table 2 below.

[0054] Table 2

[0055]

[0056]

[0057] It can be seen from Table 2 that the average grain size of the TaW13 alloy plate prepared in this embodiment is significantly lower than that of the TaW13 alloy plate prepared by the conventional process, and the tensile strength is improved, and the elongation and cross-sectional shrinkage are greatly improved.

[0058] Example 3

[0059] This embodiment includes the following steps:

[0060] Step 1: Place Ta powder, W powder and Sc2O3 powder in a mixer and mix them evenly, and press them into billets with a size (width×height×length) of 17mm×17mm×400mm. Place the billets in a vacuum carbon tube furnace for high-temperature sintering to obtain grayish white, slightly yellowish and curved sintered bars;

[0061] The particle size of the Ta powder and the W powder does not exceed 320 meshes, the particle size of the Sc2O3 powder does not exceed 500 meshes, and the mass of the Sc2O3 powder added is 0.09% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, the mass of the W powder added is 9.5% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, and the balance is Ta powder;

[0062] The high temperature sintering system is: in a vacuum degree not exceeding 5.0×10 -1Pa, firstly, the temperature is raised to 1700℃ within 3h and kept at this temperature for 5h, then raised to 2250℃ within 1h and kept at this temperature for 7h to complete the pre-alloying, and then the furnace temperature is lowered to below 80℃ before being taken out of the furnace;

[0063] Step 2: After bundling the sintered bars obtained in step 1 into electrodes, perform vacuum electron beam melting twice, wherein the speed of the first vacuum electron beam melting is 50 kg / h, the melting power is 100 kW, the speed of the second vacuum electron beam melting is 40 kg / h, the melting power is 160 kW, the speeds of the two vacuum electron beam meltings are successively reduced, and the melting vacuum degree does not exceed 1.0×10 -1 Pa, and obtain a TaW12 alloy ingot with a diameter of 90 mm;

[0064] Step 3, the TaW12 alloy ingot obtained in step 2 is divided, polished to remove surface defects and coated with a high-temperature anti-oxidation coating, placed in a silicon carbon rod resistance furnace, heated to 1230°C and kept warm for 50 minutes, and then a press is used for high-temperature multi-directional reciprocating die forging and free forging, two die-throwing and drawing are used, the inner diameter D of the die bore used in adjacent forging passes is 8mm apart, the chamfer R at the die opening is 0.5D, and after two times of upsetting and drawing, it is flattened and squared, the upsetting ratio of the forging blank is 1.5, and the final forging temperature is 900°C to obtain a forging blank;

[0065] Step 4: Use a planer to plane off 4 mm thickness from the six faces of the forging blank obtained in step 3, and then thoroughly grind away the crack defects;

[0066] Step 5: The forged blank after grinding in step 4 is completely covered with a steel plate sheath. The steel plate sheath is made of Q235 steel with a thickness of 3 mm. It is welded by argon arc welding, and then placed in a resistance muffle furnace and heated to 1000°C. The holding time is 50 minutes. The two-roll plate rolling mill is used for hot rolling with the sheath. The pass deformation is 8% and the total deformation is 74%. Then, the steel plate sheath is removed with dilute hydrochloric acid, and vacuum annealing is performed. The vacuum annealing system is: keep warm at 1400°C for 2 hours, and keep the vacuum degree not less than 5.0×10 -2 Pa, and obtain TaW12 alloy sheet.

[0067] Samples were taken from the TaW12 alloy plate prepared in this embodiment, and room temperature mechanical property tests and microstructure analyses were performed, respectively. The performance of the samples was then compared with that of the TaW12 alloy plate prepared by the conventional process widely used in the industry, i.e., sintering and smelting of Ta powder and W powder followed by extrusion, conventional forging, and rolling. The results are shown in Table 3 below.

[0068] Table 3

[0069]

[0070] It can be seen from Table 3 that the average grain size of the TaW12 alloy plate prepared in this embodiment is significantly lower than that of the TaW12 alloy plate prepared by the conventional process, and the tensile strength is improved, and the elongation and cross-sectional shrinkage are greatly improved.

[0071] Figure 1 The forging blank prepared in this embodiment is welded and rolled by steel plate sheathing. Figure 1 It can be seen that the metal under the steel plate sheath is silver and has no oxidation or cracks.

[0072] Figure 2 This is the SEM image of the tensile fracture of the TaW12 alloy plate prepared in this example. Figure 2 It can be seen that the slip phenomenon on the dimple of the tensile fracture of the TaW12 alloy plate is more obvious, and a large number of shrinkage holes appear at the bottom of the dimple, showing strong plastic deformation characteristics.

[0073] Figure 3 This is the metallographic diagram of the TaW12 alloy plate prepared in this embodiment. Figure 3 It can be seen that the structure of the TaW12 alloy plate is uniform and fine equiaxed crystals with an average grain size of about 15 μm.

[0074] Example 4

[0075] This embodiment includes the following steps:

[0076] Step 1: Place Ta powder, W powder and Sc2O3 powder in a mixer and mix them evenly, and press them into billets with a size (width×height×length) of 17mm×17mm×400mm. Place the billets in a vacuum carbon tube furnace for high-temperature sintering to obtain grayish white, slightly yellowish and curved sintered bars;

[0077] The particle size of the Ta powder and the W powder does not exceed 320 meshes, the particle size of the Sc2O3 powder does not exceed 500 meshes, and the mass of the Sc2O3 powder added is 0.08% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, the mass of the W powder added is 9.7% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, and the balance is Ta powder;

[0078] The high temperature sintering system is: in a vacuum degree not exceeding 5.0×10 -1 Pa, firstly, the temperature is raised to 1700℃ within 3h and kept at this temperature for 5h, then raised to 2300℃ within 3h and kept at this temperature for 5h to complete the pre-alloying, and then the furnace temperature is lowered to below 80℃ before being taken out of the furnace;

[0079] Step 2: After bundling the sintered bars obtained in step 1 into electrodes, perform vacuum electron beam melting twice, wherein the speed of the first vacuum electron beam melting is 45 kg / h, the melting power is 105 kW, the speed of the second vacuum electron beam melting is 35 kg / h, the melting power is 170 kW, the speeds of the two vacuum electron beam meltings are successively reduced, and the melting vacuum degree does not exceed 1.0×10 -1 Pa, and obtain a TaW12 alloy ingot with a diameter of 100 mm;

[0080] Step 3, the TaW12 alloy ingot obtained in step 2 is divided, polished to remove surface defects and coated with a high-temperature anti-oxidation coating, placed in a resistance furnace, heated to 1260°C and kept warm for 50 minutes, and then high-temperature multi-directional reciprocating die forging and free forging are performed using an air hammer, two die-throwing and drawing are used, the inner diameter D of the die bore used in adjacent forging passes is 7mm apart, the chamfer R at the die opening is 0.5D, and after two upsetting and drawing, it is flattened and squared, the upsetting ratio of the forging blank is 1.5, and the final forging temperature is 900°C to obtain a forging blank;

[0081] Step 4: Use a planer to plane off 4 mm thickness from the six faces of the forging blank obtained in step 3, and then thoroughly grind away the crack defects;

[0082] Step 5: The forged blank after grinding in step 4 is completely covered with a steel plate sheath. The steel plate sheath is made of Q235 steel with a thickness of 3 mm. Argon arc welding is adopted, and then the blank is placed in a resistance muffle furnace and heated to 1050°C. The holding time is 50 min. The blank is hot rolled with a two-roll plate rolling mill with a pass deformation of 7% and a total deformation of 70%. The steel plate sheath is then removed with dilute hydrochloric acid, and vacuum annealing is performed. The vacuum annealing system is: keep warm at 1430°C for 2 hours, and keep the vacuum degree not less than 5.0×10 -2 Pa, and obtain TaW12 alloy sheet.

[0083] Samples were taken from the TaW12 alloy plate prepared in this embodiment, and room temperature mechanical property tests and microstructure analyses were performed, respectively. The performance of the samples was then compared with that of the TaW12 alloy plate prepared by the conventional process widely used in the industry, i.e., sintering and smelting of Ta powder and W powder followed by extrusion, conventional forging, and rolling. The results are shown in Table 4 below.

[0084] Table 4

[0085]

[0086] It can be seen from Table 4 that the average grain size of the TaW12 alloy plate prepared in this embodiment is significantly lower than that of the TaW12 alloy plate prepared by the conventional process, and the tensile strength is improved, and the elongation and cross-sectional shrinkage are greatly improved.

[0087] Example 5

[0088] This embodiment includes the following steps:

[0089] Step 1: Place Ta powder, W powder and Sc2O3 powder in a mixer and mix them evenly, and press them into billets with a size (width×height×length) of 17mm×17mm×400mm. Place the billets in a vacuum carbon tube furnace for high-temperature sintering to obtain grayish white, slightly yellowish and curved sintered bars;

[0090] The particle size of the Ta powder and the W powder does not exceed 320 meshes, the particle size of the Sc2O3 powder does not exceed 500 meshes, and the mass of the Sc2O3 powder added is 0.1% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, the mass of the W powder added is 11% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, and the balance is Ta powder;

[0091] The high temperature sintering system is: in a vacuum degree not exceeding 5.0×10 -1 Pa, firstly, the temperature is raised to 1700℃ within 3h and kept at this temperature for 4h, then raised to 2400℃ within 1h and kept at this temperature for 8h to complete the pre-alloying, and then the furnace temperature is lowered to below 80℃ before being taken out of the furnace;

[0092] Step 2: After bundling the sintered bars obtained in step 1 into electrodes, perform vacuum electron beam melting twice, wherein the speed of the first vacuum electron beam melting is 30 kg / h, the melting power is 130 kW, the speed of the second vacuum electron beam melting is 25 kg / h, the melting power is 190 kW, the speeds of the two vacuum electron beam meltings are successively reduced, and the melting vacuum degree does not exceed 1.0×10 -1 Pa, and obtain a TaW13 alloy ingot with a diameter of 90 mm;

[0093] Step 3, the TaW13 alloy ingot obtained in step 2 is divided, polished to remove surface defects and coated with a high-temperature anti-oxidation coating, placed in a resistance furnace, heated to 1300°C and kept warm for 50 minutes, and then a press is used for high-temperature multi-directional reciprocating die forging and free forging, three times of die throwing and drawing are used, the inner diameter D of the die bore used in adjacent forging passes is 5mm apart, the chamfer R at the die opening is 0.5D, and after three times of upsetting and drawing, it is flattened and squared, the upsetting ratio of the forging blank is 1.3, and the final forging temperature is 900°C to obtain a forging blank;

[0094] Step 4: Use a planer to plane off 3mm thickness from the six faces of the forging blank obtained in step 3, and then thoroughly grind away the crack defects;

[0095] Step 5: The forged blank after grinding in step 4 is completely covered with a steel plate sheath. The steel plate sheath is made of Q235 steel with a thickness of 3 mm. Argon arc welding is adopted, and then the blank is placed in a resistance muffle furnace and heated to 1100°C. The holding time is 50 min. The blank is hot rolled with a two-roll plate rolling mill with a pass deformation of 5% and a total deformation of 55%. The steel plate sheath is then removed with dilute hydrochloric acid, and vacuum annealing is performed. The vacuum annealing system is: keeping at 1500°C for 3 hours, and the vacuum degree is maintained at not less than 5.0×10 -3 Pa, and a TaW13 alloy plate with a thickness of 12 mm was obtained.

[0096] Samples were taken from the TaW13 alloy plate prepared in this embodiment, and room temperature mechanical property tests and microstructure analyses were performed, respectively. The performance was then compared with that of the TaW10 alloy plate prepared by the conventional process widely used in the industry, i.e., sintering and smelting of Ta powder and W powder followed by extrusion, conventional forging, and rolling. The results are shown in Table 5 below.

[0097] Table 5

[0098]

[0099] It can be seen from Table 5 that the average grain size of the TaW13 alloy plate prepared in this embodiment is significantly lower than that of the TaW13 alloy plate prepared by the conventional process, and the tensile strength is improved, and the elongation and cross-sectional shrinkage are greatly improved.

[0100] Example 6

[0101] This embodiment includes the following steps:

[0102] Step 1: Place Ta powder, W powder and Sc2O3 powder in a mixer and mix them evenly, and press them into billets with a size (width×height×length) of 17mm×17mm×400mm. Place the billets in a vacuum carbon tube furnace for high-temperature sintering to obtain grayish white, slightly yellowish and curved sintered bars;

[0103] The particle size of the Ta powder and the W powder does not exceed 320 meshes, the particle size of the Sc2O3 powder does not exceed 500 meshes, and the mass of the Sc2O3 powder added is 0.07% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, the mass of the W powder added is 7.9% of the total mass of the Ta powder, the W powder and the Sc2O3 powder, and the balance is Ta powder;

[0104] The high temperature sintering system is: in a vacuum degree not exceeding 5.0×10 -1 Pa, firstly, the temperature is raised to 1700℃ within 3h and kept at this temperature for 4h, then raised to 2100℃ within 1h and kept at this temperature for 6h to complete the pre-alloying, and then the furnace temperature is lowered to below 80℃ before being taken out of the furnace;

[0105] Step 2: After bundling the sintered bars obtained in step 1 into electrodes, perform vacuum electron beam melting twice, wherein the speed of the first vacuum electron beam melting is 60 kg / h, the melting power is 70 kW, the speed of the second vacuum electron beam melting is 45 kg / h, the melting power is 115 kW, the speeds of the two vacuum electron beam meltings are successively reduced, and the melting vacuum degree does not exceed 1.0×10 -1 Pa, and obtain a TaW10 alloy ingot with a diameter of 100 mm;

[0106] Step 3, the TaW10 alloy ingot obtained in step 2 is divided, polished to remove surface defects and coated with a high-temperature anti-oxidation coating, placed in a resistance furnace, heated to 1100°C and kept warm for 50 minutes, and then high-temperature multi-directional reciprocating die forging and free forging are performed using an air hammer, two die-throwing and drawing are used, the inner diameter D of the die bore used in adjacent forging passes is 10 mm apart, the chamfer R at the die opening is 0.4D, and after two upsetting and drawing, it is flattened to form a square, the upsetting ratio of the forging blank is 1.6, and the final forging temperature is 900°C to obtain a forging blank;

[0107] Step 4: Use a planer to plane off 3mm thickness from the six faces of the forging blank obtained in step 3, and then thoroughly grind away the crack defects;

[0108] Step 5: The forging blank after grinding in step 4 is completely covered with a steel plate sheath. The steel plate sheath is made of Q235 steel with a thickness of 2 mm. Argon arc welding is adopted, and then the forging blank is placed in a resistance muffle furnace and heated to 800°C. The holding time is 50 min. The forging blank is hot rolled with a four-roll plate rolling mill with a deformation of 15% per pass and a total deformation of 78%. The steel plate sheath is then removed with dilute hydrochloric acid, and vacuum annealing is performed. The vacuum annealing system is as follows: the temperature is kept at 1280°C for 1 hour, and the vacuum degree is maintained at not less than 5.0×10 -3 Pa, and a TaW10 alloy plate with a thickness of 8.5 mm was obtained.

[0109] Samples were taken from the TaW10 alloy plate prepared in this embodiment, and room temperature mechanical property tests and microstructure analyses were performed, respectively. The performance of the samples was then compared with that of the TaW10 alloy plate prepared by the conventional process widely used in the industry, i.e., sintering and smelting of Ta powder and W powder followed by extrusion, conventional forging, and rolling. The results are shown in Table 6 below.

[0110] Table 6

[0111]

[0112] It can be seen from Table 6 that the average grain size of the TaW10 alloy plate prepared in this embodiment is significantly lower than that of the TaW10 alloy plate prepared by the conventional process, and the tensile strength is improved, and the elongation and cross-sectional shrinkage are greatly improved.

[0113] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a fine-grained, high-plasticity Ta-W alloy sheet, characterized in that: The method comprises adding Sc2O3 powder to Ta-W alloy raw materials and mixing them to prepare sintered bars, then performing electron beam melting, and then performing multi-directional reciprocating die forging, free forging, and jacket rolling to prepare Ta-W alloy plates; the material of the Ta-W alloy plates is TaW10, TaW12 or TaW13 alloys with high W content.

2. The method for preparing a fine-grained high-plasticity Ta-W alloy sheet according to claim 1, characterized in that: The method comprises the following steps: Step 1: Place Ta powder, W powder and Sc2O3 powder in a mixer and mix them evenly, and press them into billets, and place the billets in a vacuum carbon tube furnace for high-temperature sintering to obtain sintered billets; Step 2: subjecting the sintered bar obtained in step 1 to electron beam melting twice to obtain a Ta-W alloy ingot; Step 3: split the Ta-W alloy ingot obtained in step 2, and then perform high-temperature multi-directional reciprocating die forging and free forging using a forging hammer or a press to obtain a forging blank; Step 4, machining the forging blank obtained in step 3 to remove defects; Step 5: The forging blank after the defects are removed in step 4 is covered with a steel plate for welding, and then hot rolled to obtain a Ta-W alloy plate.

3. The method for preparing a fine-grained high-plasticity Ta-W alloy sheet according to claim 2, characterized in that: In step 1, the particle size of the Ta powder and the W powder does not exceed 320 mesh, the particle size of the Sc2O3 powder does not exceed 500 mesh, and the mass of the Sc2O3 powder added is 0.05% to 0.1% of the total mass of the Ta powder, the W powder and the Sc2O3 powder.

4. The method for preparing a fine-grained high-plasticity Ta-W alloy sheet according to claim 2, characterized in that: The high temperature sintering system in step 1 is: in a vacuum degree not exceeding 5.0×10 -1 Pa, first raise the temperature to 1700°C within 3 hours and keep it for 4 hours, then raise the temperature to 2100°C~2400°C within 1 hour and keep it for 6 hours~8 hours to complete pre-alloying, and then drop the furnace temperature to below 100°C before taking out of the furnace.

5. The method for preparing a fine-grained high-plasticity Ta-W alloy sheet according to claim 2, characterized in that: The sintered bars in step 2 are bundled into electrodes and then subjected to vacuum electron beam melting twice, wherein the speed of the first vacuum electron beam melting is 30kg / h to 60kg / h, and the speed of the second vacuum electron beam melting is 25kg / h to 45kg / h, and the speeds of the two vacuum electron beam melting are successively reduced, the melting power is 70kW to 190kW, and the melting vacuum degree does not exceed 1.0×10 -1 Pa.

6. The method for preparing a fine-grained high-plasticity Ta-W alloy sheet according to claim 2, characterized in that: The high-temperature multi-directional reciprocating die forging plus free forging in step three is heated to 1100°C~1300°C in a resistance furnace, the holding time is 50min, the final forging temperature is 900°C, and the multi-directional die forging is performed at least twice using a drop die. The inner diameter D of the drop die used in adjacent forging passes is 5mm~10mm apart, the chamfer R at the drop die opening is (0.4~0.5)D, and the upsetting ratio of the forging blank is less than 1.

7.

7. The method for preparing a fine-grained high-plasticity Ta-W alloy sheet according to claim 2, characterized in that: In step 4, a planer is used to plane off the six faces of the forging blank by 3 mm to 5 mm in thickness until the oxide scale and crack defects are completely removed.

8. The method for preparing a fine-grained high-plasticity Ta-W alloy sheet according to claim 2, characterized in that: The steel plate sheath in step five is made of Q235 steel with a thickness of 2mm to 3mm and is welded by argon arc welding; the heating temperature of the hot rolling is 800°C to 1100°C, the insulation time is 50min, the deformation per pass is 5% to 15%, and the rolling equipment used is a two-roll or four-roll plate rolling mill.

9. The method for preparing a fine-grained high-plasticity Ta-W alloy sheet according to claim 2, characterized in that: After hot rolling in step 5, the steel plate jacket is removed by using dilute hydrochloric acid, and then vacuum heat treatment is performed. The vacuum heat treatment system is: heat preservation at 1280℃~1500℃ for 1h~3h, and the vacuum degree is maintained at 5.0×10 - 2 Pa~5×10 -4 Pa.

Citation Information

Cited By

  • Tantalum-tungsten-based nano composite target material, film and application of tantalum-tungsten-based nano composite target material

    CN122279495A